2018
DOI: 10.1007/s13197-018-3220-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of plum fruit maturity by image processing techniques

Abstract: Maturity is the key factor which determines the storage life and ripening quality of fruits. In order to provide marketing flexibility and to guarantee the acceptable eating quality to the buyer it is very critical to determine the right maturity stage. Maturity indices are also important for trade regulation, marketing strategy and for the efficient use of labor and resources. The proposed system is based on implementation of image processing techniques on the JPEG images of different maturity stages of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 14 publications
2
19
0
1
Order By: Relevance
“…Therefore, these results consistently showed that color description by quantifying pixel values was a method that exceedingly improves color differentiation in plants [22]. R, G, and B pixel values were efficient parameters for food quality determination in sweetpotato, as previously reported in other crops such as quinoa [16], and for fruit ripening quality in mango [12], citrus [19], and plum [21]. In this study, low B pixel values were found in pigmented genotypes (yellow, orange, and purple-fleshed storage roots) that, beyond their pigments, were also related to ash and protein accumulation, especially in yellow-orange genotypes.…”
Section: Discussionsupporting
confidence: 81%
“…Therefore, these results consistently showed that color description by quantifying pixel values was a method that exceedingly improves color differentiation in plants [22]. R, G, and B pixel values were efficient parameters for food quality determination in sweetpotato, as previously reported in other crops such as quinoa [16], and for fruit ripening quality in mango [12], citrus [19], and plum [21]. In this study, low B pixel values were found in pigmented genotypes (yellow, orange, and purple-fleshed storage roots) that, beyond their pigments, were also related to ash and protein accumulation, especially in yellow-orange genotypes.…”
Section: Discussionsupporting
confidence: 81%
“…Guzman et al (2015) studied the maturity index of olives using the CIELAB coordinates of the olives. Similarly, Kaur et al (2018) estimated the maturity of plumps using the RGB coordinates. In this case, high correlations were found between the R/G ratio and TSS.…”
Section: Introductionmentioning
confidence: 99%
“…There are currently very little studies that have determined the optimum harvest maturity of 'Horvin' plums. In most cases, these determinations have been carried out subjectively, based only on the size and peel color of the fruits, resulting in inconsistent organoleptic characteristics when marketing the product (Kaur, Sawhney, and Jawandha, 2018). This is the cause for the negative perception of the cultivar in a market with high demands and requirements regarding fruit quality (Kader, 2008).…”
Section: Introductionmentioning
confidence: 99%